EGO SINTONIK TOKOH-TOKOH HOMOSEKSUAL DALAM NOVEL INDONESIA MODERN - Iswadi Bahardur (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Various human  behavior in  life is the  result  of conflict and reconciliation of aspects of personality called the id, ego, and superego. Unbalance function of these aspects will result in the emergence of deviant behavior. The uncontrolled aspect of ego causes people do not able to consider the feasibility of actions in terms of moral values, tends behalf of self pleasure without measure the value of good and bad. Homosexual behavior is one of theexamples of deviant behavior in human is caused by uncontrolled ego aspect by another aspect of personalities.One  of  the  phenomenon  in  modern  Indonesian  novels  is  rampant  homosexual themes which also being warmly discussed in various countries in the world now. In reality, few  countries  in  the  world  even  has  legalized  homosexual  marriage.  The  emergence  of homosexual themes in reality imaginative novels of modern Indonesian literature indicates that it reflects the problems that raged in the community in which the work was created.This study aimed to describe the human syntonic ego problem with homosexual behavior, especially the characters contained in the novels of modern Indonesia. The results showed  that  homosexual  characters,  gay  (homosexual  designation  for  men)  and  lesbian (homosexual designation for women) in the novels that became the source of the data has syntonic ego. The sexual orientation of these characters are deviate, like the same sex. The characters are comfortable with their sexual orientation, not in conflict with himself, and not trying to change their sexual orientation to be normal.